The Normative Conceptions of Right and H. Kelsen’s Theory of Law - Šerpytytė, Rita (Problemos, 1987)
In the article H. Kelsen’s theory of law is discussed. The origins of the theory are traced back to classical positivism and neo-Kantian philosophy. It is shown that H. Kelsen pretends to solve the problem of law by the way of theoretical dissolution of the contradiction between spheres of being and necessity. The pretension is blamed as idealistic one.